(untitled) (Research, Society and Development, 2021)
Studies on dental anatomy and internal morphology of the root canal system are important to optimize endodontic therapy. Knowledge of variations in the number of channels, number of roots, horizontal dimensions and channel width increase the understanding and mastery of the anatomy for the clinician. The present study aims to describe the morphometric analysis of lower incisors through computerized microtomography. A total of 47 (n = 47) permanent lower incisors had their internal anatomy evaluated through three-dimensional computerized microtomography with parameters of standardized acquisition, reconstruction and analysis. When evaluating the presence of two root canals at the level of the middle and apical thirds, a total of 3 elements (6.4%) were found. The most prevalent channel format was oval long channels (47.7%), followed by flat channels (34.1%). No irregular channels found. By the present study it was possible to conclude that the most prevalent canal format in permanent inferior incisors is the long oval, and no irregular channels were found.